2023
DOI: 10.3390/agriculture13040857
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mycorrhiza Fungi and Various Mineral Fertilizer Levels on the Growth, Yield, and Nutritional Value of Sweet Pepper (Capsicum annuum L.)

Abstract: Mycorrhizal fungi can increase the effectiveness of a mineral fertilizer top dressing, positively affecting sweet pepper yield and quality. For this reason, an experiment was carried out between 2014 and 2016 to study the effect of top dressing doses and the inoculation of the root system with mycorrhizal fungi on the growth and yield of sweet pepper and the content of nutrients and macro- and microelements in the fruits. Root inoculation with Arbuscular Mycorrhizal Fungi (AMF) and mineral fertilizer doses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
2
3
0
Order By: Relevance
“…From the obtained results, the treatments of mycorrhizal inoculation and humic acid significantly increased plant growth parameters, yield, and harvest index, but the mycorrhizal inoculation combined with humic acid had better effects on growth parameters. The positive effects of mycorrhizal inoculation and humic acids on plant growth were also confirmed by prior studies (Franczuk et al, 2023;Khafagi et al, 2018;Khan et al, 2018;Sadhana, et al 2014). Understanding the role of humic acids on crop performance has been reviewed by Ampong et al (2022), revealing that HA application has potentially significant effects on crop agronomic performance and soil quality parameters.…”
Section: Discussionsupporting
confidence: 76%
“…From the obtained results, the treatments of mycorrhizal inoculation and humic acid significantly increased plant growth parameters, yield, and harvest index, but the mycorrhizal inoculation combined with humic acid had better effects on growth parameters. The positive effects of mycorrhizal inoculation and humic acids on plant growth were also confirmed by prior studies (Franczuk et al, 2023;Khafagi et al, 2018;Khan et al, 2018;Sadhana, et al 2014). Understanding the role of humic acids on crop performance has been reviewed by Ampong et al (2022), revealing that HA application has potentially significant effects on crop agronomic performance and soil quality parameters.…”
Section: Discussionsupporting
confidence: 76%
“…So, the synergic effect of using vermicompost with the biofertilizers may result from providing the tomato plants, particularly those grown in sandy soil (Table 2) with the essential soluble nutrients from vermicompost, Phosphate-solubilizing bacteria, Vascular arbuscular mycorrhizal, and secreting stimulating substances such as auxins, cytokinins, gibberellins, amino acids and vitamins from vermicompost and Azotobacter, beside increasing the performance of the plant under biotic and abiotic stresses. The stimulative effect on yield, mineral content, chlorophyll contents, and yield were previously reported by Nanjundappa et al (2019), Ziane, et al (2021), Franczuk et al (2023 The treatments of Vermi + Azoto + Azos + PSB, Vermi + Azoto + Azos +VAM, and Vermi + Azoto + Azos + PSB + VAM significantly increased equatorial diameter and significantly improved fruit quality, showing the highest values of total sugar, TSS, ascorbic acid, and lycopene, but they reduced ß-carotene. The present results are in agreement with the previous findings which showed that strawberry plants fertilized with Azotobacter at 7 kg/ha produced berries with maximum width, TSS total sugars, and ascorbic acid with minimum titratable acidity in comparison to other treatments (Anurag and Tripathi, 2020).…”
Section: Discussionsupporting
confidence: 70%
“…Inoculations with P-solubilizing bacteria and mycorrhizal fungi significantly increased vitamin C in tomato fruits (Chouyia et al, 2022). Mycorrhiza application resulted in significant changes in the total sugar content of pepper fruits (Franczuk et al, 2023). Similarly, using sand: vermicompost (2:1) + Azotobactor increased TSS and ascorbic acid in strawberry fruits as compared with sand alone (Reddy et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivation of bell pepper and tomato has been steadily increasing due to the growing public demand. Pepper and tomato fruits are a rich source of minerals, vitamins, and antioxidants, including carotenoids (β-carotenoids and lycopene) and vitamins (A, C, and E) [2,3]. These compounds have been reported to help in preventing not only cancer but also cardiovascular diseases [4].…”
Section: Introductionmentioning
confidence: 99%